Research Paper: Design and Fabrication of Flexible Graphene Electrode with Visible Laser - Hediye Pazokian; Maryam Bahreini; Fatemeh Rajabi (فیزیک کاربردی ایران)
In this paper, the fabrication of graphene electrodes on Polyimide film with laser induced graphene phenomenon was investigated. For this purpose, a visible laser with a wavelength of 445 nm was used to create graphene on the surface. The formation of the graphene on the surface following irradiation was tested by Raman spectroscopy and X-ray diffraction of the irradiated sample. An electrical multimeter and a scanning electron microscope were used to investigate the effect of irradiation parameters such as laser power, laser irradiated lines overlapping, and laser scanning velocity on the electrical resistance and the surface morphology, respectively. The results indicate the formation of porous graphene with different structures on the surface by the laser laser-induced graphene phenomenon. The minimum electrical resistance of ~80 ohms was achieved with a specific irradiation condition. However, surface morphology is an important parameter affecting the quality of the electrodes in many applications, such as energy storage devices. According to this research, the irradiation conditions should be optimized for the formation of an electrode for the desired application.